What can we learn about wildlife killed by vehicles from a citizen science project? A comparison of scientific and amateur tropical roadkill records (UNED Research Journal, 2018)
In 1995, Costa Rica had one of the first citizen science projects on roadkills, which identified the most frequent species and their rates by road length, and currently it has one of the largest iNaturalist projects on the same subject. Here I assess what information can be extracted from this type of project and how results compare with those from professionals. I analyzed over 900 records from Fauna Silvestre en Carreteras de Costa Rica, from October 2013 through August 2017. There was no sexual difference in participation or productivity, but per capita output was 12 times higher than in the Brazilian CBEE project. Some species suffered higher mortality during reproduction, while the anteater T. mexicana suffered more in the dry season, when food was scarce. Roadkills matched seasonal changes in traffic routes and the geographic distribution of records in relation to urban areas reflected the ecology of each species. At least for this case, citizen science can provide reliable data about species frequency in roadkills, and data were detailed enough to identify seasonal and geographic differences at the species level for the mammals and reptiles that made up the majority of records.
Keywords: roadkill; road mortality; iNaturalist; citizen science